Ellis Ballou correspondence - Ballou, Ellis, -1903.
ALS (29 January 1853; Newton Falls, Ohio) from Ballou to S. M. Parmely, Western Reserve Eclectic Institute, Hiram, Ohio, concerning a talk given by Joseph Mason, a fugitive slave. Ballou also discusses women's suffrage and other matters.
Editor and publisher. Cousin of President James A. Garfield.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Mason, Joseph, -- active 1853.; Parmely, S. M. -- Correspondence; Fugitive slaves; Slavery; Women -- Suffrage; Editors; Publishers